Data Mining Pengelompokan Akta Nikah Berdasarkan Usia Nikah atau Domisili Menggunakan Metode Clustering: Studi Kasus Kemenag Langkat - Nurlaila Nurlaila (MES Bogor, 2022)
A park in a limited sense is a plot of land that is arranged in such a way that it has beauty, comfort, and security for the owner or user. Based on the scale and shape, the park can be called a garden, park, or landscape. Now the park is not only filled with plants or large trees but has varied, one of which is by making ornamental grasses. A decision support system is used in the selection of grass types to make it easier for users to decide which grass to use for gardening. The VIKOR method is a Multi-Criteria Decision Making (MCDM) method that can be used to select more than one criteria. it can be seen that the first alternative to choose the best grass for gardening is peking, swiss and pescue grass with a value of Q = -0.6 and 0.05 and has the right to be recommended as a type of grass for gardening. Keywords: Park, Vikor Method, Decision Making System